The influence of conservatism and overconfidence on investment decisions among investors in Nepali stock market - Giri, Bishnu; Adhikari, Sagar (Journal of Emerging Management Studies, 2023)
Purpose - Adopting behavioral finance to identify the investors’ investment decision is instrumental in developing insight into the financial and economic activity of the investors. This paper attempts to examine how conservatism and overconfidence influence investors’ investment decisions in Nepali share market. Design/methodology/approach - The research followed the questionnaire method where structured self-monitored close questions were surveyed from 335 respondents via internet. To analyze the data, SPSS software was used, and to test the direct effects of the hypotheses, covariance base analysis (CB-SEM) was applied. Findings and Conclusion - The outcomes of the regression analysis depict that the conservatism of Nepali investors has a considerable positive impact on their investment decisions. It has also revealed that overconfidence had an insignificant role in investment decisions, which indicates investors do not show overconfidence while investing in the stock market. Originality/value - Conservatism and overconfidence of stakeholders in the share market by applying behavioral theory in Nepal are largely unexplored. Because it is one of the few studies that examine the influence of conservatism in Nepal, this study occupies a precarious position in Nepali research on investment decision in the share market.